Proceedings. 10th IEEE International Workshop on Future Trends of Distributed Computing Systems, 2004. FTDCS 2004.
DOI: 10.1109/ftdcs.2004.1316598
|View full text |Cite
|
Sign up to set email alerts
|

Smart phone: an embedded system for universal interactions

Abstract: In this paper, we present a system architecture that allows

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Portable devices refer to general-purpose pervasive mobile devices, such as smart phones [16], or PDAs. While there is no commonly-accepted universal device platform, mobile phones have the greatest potential to replace all the different devices we currently carry in our pockets [17] because of emerging mobile phone technologies which provide various styles of networking capability through which the Grid can be accessed. Proxy devices might be a desktop computer or a small server available for nearby portable devices via the local wireless network, providing a relatively resource-rich execution environment and network connectivity compared to portable devices.…”
Section: System Overviewmentioning
confidence: 99%
“…Portable devices refer to general-purpose pervasive mobile devices, such as smart phones [16], or PDAs. While there is no commonly-accepted universal device platform, mobile phones have the greatest potential to replace all the different devices we currently carry in our pockets [17] because of emerging mobile phone technologies which provide various styles of networking capability through which the Grid can be accessed. Proxy devices might be a desktop computer or a small server available for nearby portable devices via the local wireless network, providing a relatively resource-rich execution environment and network connectivity compared to portable devices.…”
Section: System Overviewmentioning
confidence: 99%
“…Iftode et al [3] identified the need for a simple, universal solution to control different applications in the environment of the user, which end-users are likely to accept easily. Many studies in smart home environments have proved that users can easily interact with their context using handheld devices.…”
Section: Introductionmentioning
confidence: 99%
“…Different kinds of interactions between mobile devices and the environment have been studied (Iftode et al, 2004). The previous chapter detailed in Section 2.2 the technologies, infrastructures and languages to bridge the gap between the physical and the digital world.…”
Section: Analysis and Discussionmentioning
confidence: 99%